The influence of dimension and relation of heat energy on the size of welded I-girder diflection - Vlastimir, Palić; Sabo, Bela (Journal of Production Engineering, 1984)
In this paper three factorial extreme experiment was applied. For determination of girder deflection resulted by welding, this type of experiment requires only 24 experimental girders insted of 300 girders which are necessary in case of complete experiment application.